Determinan Profitabilitas Dan Ukuran Perusahaan Terhadap Harga Saham Pada Perusahaan Property Dan Real Estate - Vini Alvianita; Muhammad Rivandi (Pusat Riset dan Inovasi Nasional, 2023)
The company’s stock price isthe closing price which is formed due to the interaction between buyers and sellers. This study aims to determine the effect of profitability using the calculation of Return On Assets (ROA), and company size using the caculation of Ln Total Assets on the company’s stock price as measured by the closing price of each company. The population in this study were Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021 which were selected using the purposive sampling method and obtained 10 Property dan Real Estate companies within 5 years so that 50 samples were observed. The data analysis method used in this study is the panel data regresion model. Based on the result of testing the hypotesis, that profitability has a positive effect while company size has no effect on stock prices.